COVID-19 living evidence synthesis #6 (version 6.41): What is the efficacy and effectiveness of available COVID-19 vaccines in general and specifically for variants of concern? - Iorio, A; Little, J; Linkins, L; Abdelkader, W; Bennett, D; Lavis, JN (My University, 2022)
An in-depth synthesis of what is known, based on the best available research evidence from around the world (i.e., evidence syntheses) and local research evidence (i.e., single studies), about the efficacy and effectiveness of available COVID-19 vaccines in general and specifically for variants of concern.
Keywords: efficacy; effectiveness; COVID-19; vaccines; variants